Kedudukan Antar Pesan Dakwah: Studi Ceramah Ustazah Mumpuni Handayekti Dalam Program Aksi Asia - Alan Surya; Refita Prostyaningtyas (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
This paper examines the position between the messages of akidah, sharia and morals in a da’wah. This paper is based on the assumption that da’wah message is the spirit of da'wah itself. Many previous research of da’wah message has found the descriptions of da’wah message in the religious lectures, both quantitatively and qualitatively, while further analysis limited to finding dominant or distinctive da'wah messages. It is still necessary to analyze the position between all kinds of da'wah messages so that Islamic teachings can be fully understood. This paper aims to examine the position of various da'wah messages such as aqidah, sharia and morals in religious lectures. So that it can be useful for preachers when composing da'wah messages before speaking it. This research is an inductive qualitative research, using three religious lectures of Ustadzah Mumpuni Handayekti in the Aksi Asia program as research objects. The result of this study are: 1) Aqidah message is the main and the basis for sharia and morals message, 2) The logical consequences for people who have faith is to obey sharia and morals teachings, 3) The position of sharia and moral messages is the same (not necessarily sequential or concurrent), 4) Ustadzah Mumpuni Handayekti has succeeded in linking various da'wah messages and packaging them well in religious lectures, 5) However, it is necessary to add the direction of the da'wah message which is not only to form a good person but also a good society, and it requires scientific and systematic teaching methods.